Valorization of coffee parchment waste from agroforestry systems via downdraft gasification for renewable syngas production - Gusti Wijaya; Bugae Park; Bainah Sari Dewi; Wahyu Hidayat (Global Forest Journal., 2026)
Coffee-based agroforestry systems generate large quantities of coffee parchment, which is commonly underutilized and becomes waste after processing. To date, there is no information regarding its effective utilization. Therefore, to improve its quality and increase its economic value, the production of renewable syngas through gasification is a promising approach. Gasification experiments were conducted using a downdraft gasifier reactor. Syngas composition was measured using a Portable Infrared Syngas Analyzer.  Moisture content (MC) and proximate analysis (including volatile matter (VM), ash content (AC), and fixed carbon (FC), of both biomass and gasification solid by-products in the form of biochar were performed. The syngas composition of coffee parchment consisted of 4.95% CO, 5.81% CO₂, 0.56% CH₄, 4.24% H₂, and 13.19% O₂. The LHV of the produced syngas ranged from 256.15 to 417.19 kcal/m³ during the gasification process. The MC, VM, AC, and FC of coffee parchment were 14.85%, 11.94%, 4.85%, and 83.21%, whereas those of the solid by-product were 26.85%, 8.63%, 6.81%, and 84.56%, respectively. The relatively high fixed carbon content indicates that coffee parchment has promising characteristics as a solid bioenergy feedstock. However, the dominance of oxygen in the syngas composition suggests that airflow conditions in the gasifier were unstable, affecting the quality of the produced gas. In conclusion, coffee parchment waste from agroforestry systems has potential as a renewable energy resource, although optimization of gasification operating conditions is required to improve syngas quality and energy efficiency